2020
DOI: 10.1002/aenm.201904072
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Palladium‐Gold Nanochains with Periodic Concave Structures as Superior ORR Electrocatalysts and Highly Efficient SERS Substrates

Abstract: Unique palladium‐gold hollow nanochains (PdAu HCs) with 1D architecture and an ultrathin Pd‐rich skin exhibit fantastic oxygen reduction reaction (ORR) enhancements due to their high conductivity, structural stability, and maximized atomic utilization. More importantly, such PdAu HCs possess periodic concave structures that boost ORR performance. These structures readily form high‐density high‐index facets, and fewer arc edges. Concave structures can deliver strong strain effects and surface charge accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 72 publications
2
60
0
Order By: Relevance
“…The family of metal-nitrogen complex carbon (M–N–C) materials has high conductivity and unique metal–ligand interaction, which have been regarded as the most promising alternatives to commercial Pt/C because of their outstanding performance in activation of oxygen 26 30 . According to the latest research, due to the improvement in the structural stability of the active center and the modulation of the electron cloud, bimetallic particles show higher activity and stability when compared with monometallic atomic particles 31 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The family of metal-nitrogen complex carbon (M–N–C) materials has high conductivity and unique metal–ligand interaction, which have been regarded as the most promising alternatives to commercial Pt/C because of their outstanding performance in activation of oxygen 26 30 . According to the latest research, due to the improvement in the structural stability of the active center and the modulation of the electron cloud, bimetallic particles show higher activity and stability when compared with monometallic atomic particles 31 33 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the MCT was enhanced by adjusting the impedance matching and attenuation constant between magnetic and dielectric materials of microwaveocaloric sensitivity agents, which can absorb MV energy and convert it into thermal energy. Che et al developed the enhanced coupling of the electronic field to facilitate the chemical activity of the magnetic nanoparticles 16,17 and pioneer the investigation of chemical reaction mechanisms in the nanometer devices 18 . Magnetic iron oxide (Fe 3 O 4 ) nanoparticles not only have large magnetic loss 19 , and thus produce huge magnetico calor under MV excitation, but also have already been approved by the US Food and Drug Administration for medical use 20 .…”
mentioning
confidence: 99%
“…It was also found that the higher binding energy on the surface Pt atoms in Pt 4 Ni-skin may also explain the high stability of the PtNi-BNSs/C catalyst with only slight decay in activity after 50 k cycles because the defects with high surface energy were enclosed in the nanocages. Similar to this unique hollow nanochain structure, Che et al obtained 1D Pd-Au hollow nanochains with an ultrathin Pdrich skin through displacement reaction (Jiao et al, 2020). The PdAu hollow nanochains (HCs) possessed periodic concave structures that displayed boosted ORR performance.…”
Section: General Effectmentioning
confidence: 98%